Analysis of Import Dependence and Its Relationship with Regional Economic Development in Russia: The Case of the Volga Federal District - Burganov , Rafis T.; Elshin , Leonid A.; Abdrakhmanova , Dilara R.; Dinmukhametova , Aliya A. (Economy of Regions, 2026)
In the context of rising external sanctions, understanding the link between import supply disruptions and regional economic development is increasingly important. To address this task, this article proposes methods for identifying critical imports and constructing a statistical model to assess the degree of dependence between these variables. The study hypothesizes that a statistically significant relationship exists between regional critical imports and indicators of regional economic dynamics under external constraints. The research methodology is based on systematization, grouping, and panel data regression modelling with robust cluster standard errors. The empirical base includes statistical data for regions of the Volga Federal Okrug for 2011–2021. The sample comprises import volumes for 103 Commodity Nomenclature of Foreign Economic Activity (TN VED) codes. The findings reveal the key components that form the conceptual framework for determining critical imports: the role of imports in generating regional value added; the share of imports originating from unfriendly countries; and the classification of imports as final or intermediate goods. The relationship between critical imports and the gross regional product (GRP) of the regions under study is subsequently analysed. The estimated elasticity coefficient for the variable “Volume of critical imports” in the model, controlling for education level, investment, and consumer expenditure, is 0.0326. This relationship is moderate compared to other explanatory variables. A limitation of the study is its reliance on official statistical data, which has been inconsistently published for Russian regional imports since 2022.